Preparing In-Service Teacher Using Dynamic Geometry Software - Setyawan, Fariz; Kristanto, Yosep Dwi; Ishartono, Naufal (International Journal of Engineering and Technology, 2018)
The use of technology is essential in teaching and learning process. Many researchers have already been implemented Dynamic Geometry Software (DGS) in teaching and learning process. Given the importance of DGS, it is necessary for in-service teachers to use the software in their teaching and learning. Hence, it is important to prepare in-service teacher in utilizing DGS through the professional development program. This is a qualitative research which describes a professional development program to facilitate in-service teachers in utilizing DGS. Both questionnaire and review measured in-service teachers’ perceptions, knowledge and skills transfer, and impact for their practice. From the findings, four of five in-service teachers recognized that they can interact with geometric figures to move on to the next level by using DGS. The teachers felt that DGS has helped them to understand the mathematics concept and demonstrate their understanding in front of the class. Besides, DGS does not only offer opportunities for teachers and students to use them both at home and in the classroom, but they also provide a means for developing support and user communities reaching across borders especially in understanding of geometrical transformation. It has contributed that the teachers easily recognize the geometrical shapes interpretations dynamically on DGS.